2021
DOI: 10.2217/fon-2021-0304
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Utility of the Systemic Immune-Inflammation Index for Predicting Survival in Esophageal Squamous Cell Carcinoma after Radical Radiotherapy

Abstract: Aim: To explore the clinical utility of the systemic immune-inflammation index (SII) for predicting the prognosis of esophageal squamous cell carcinoma (ESCC). Patients & methods: After calculating the SII in 180 patients with ESCC, the relationship between SII values and the pre-/post-radiotherapy SII ratio and overall survival was determined. Results: The median overall survival was 649 days for the entire group and 909 and 466 days for the high and low pre-/post-radiotherapy SII ratio groups, respective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Contrary to neutrophils and platelets, T-lymphocytes have been shown to inhibit tumor proliferation and metastasis, induce cytotoxic cell death, and foster antitumor immune responses ( 32 ). In recent years, a growing number of studies have demonstrated the predictive value of SII in patients with ESCC undergoing surgery and neoadjuvant therapy ( 33 36 ). However, limited studies are available that use delta-SII to predict the efficacy for any tumor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Contrary to neutrophils and platelets, T-lymphocytes have been shown to inhibit tumor proliferation and metastasis, induce cytotoxic cell death, and foster antitumor immune responses ( 32 ). In recent years, a growing number of studies have demonstrated the predictive value of SII in patients with ESCC undergoing surgery and neoadjuvant therapy ( 33 36 ). However, limited studies are available that use delta-SII to predict the efficacy for any tumor.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al. found that the pre-/post-RT SII ratio and mid-RT SII ratio were potentially effective markers for predicting ESCC prognosis ( 33 ). Similarly, in this study, an elevated delta-SII, referring to the changes in SII before and during RT, indicated worse short-term efficacy in patients with advanced ESCC who received radioimmunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, a total of 8 retrospective studies were included in this meta-analysis after reviewing the full texts. [26][27][28][29][30][31][32][33] The detailed literature process was presented in Figure 1.…”
Section: Literature Search and Selectionmentioning
confidence: 99%
“…All 8 included studies explored the predictive role of pre-radiotherapy SII for OS of Chinese ESCC patients. [26][27][28][29][30][31][32][33] The pooled results demonstrated that elevated SII was significantly associated with worse OS (HR = 1.59, 95% CI: 1.24-2.02, P < .001; I 2 = 75.1%, P < .001) (Fig. 2).…”
Section: The Association Between Pre-radiotherapy Sii and Long-term S...mentioning
confidence: 99%
See 1 more Smart Citation